Three-Component Reaction of Homophthalic Anhydride with Carbonyl Compounds and Ammonium Acetate: New Developments - Safrygin, Alexander; Bakulina, Olga; Dar’in, Dmitry; Krasavin, Mikhail (Synthesis, 2020)
The earlier described reaction of homophthalic anhydrides with aromatic ketones and ammonium acetate was tested for cyclic ketones (yielding spirocyclic motifs) and aliphatic aldehydes. In contrast to previous findings, the reaction was found to require no catalyst at all and to be applicable, in the non-catalyzed format, to these new carbonyl substrates as well as aromatic ketones. The reaction typically proceeds with high diastereoselectivity; if not, the initial diastereomeric mixture can be quantitatively equilibrated into a single, trans-diastereomer on treatment with aqueous base.
Keywords: Castagnoli–Cushman reaction; homophthalic anhydride; tetrahydroisoquinolonic acids; catalyst-free; spirocyclic compounds; diastereoselectivity